Biostimulant in the production of lawn seedlings and plant growth regulators in the development of Carpet grass - dos Santos, Patrick Luan Ferreira [UNESP]; Tavares, Armando Reis; Prates, Adrielle Rodrigues [UNESP]; do Nascimento, Matheus Vinícius Leal [UNESP]; Costa, João Victor [UNESP]; de Godoy, Leandro José Grava [UNESP]; Zabotto, Alessandro Reinaldo; Bôas, Roberto Lyra Villas [UNESP] (FapUNIFESP (SciELO), 2024)
Biostimulants such as seaweed extract can be strong allies in the formation of lawn plugs, as they assist in several physiological processes in the plant. At the same time, shoot mowing is the main factor in the maintenance cost of turfgrasses, and there is a search for alternatives to mechanical management without compromising aesthetic quality, such as the use of plant growth regulators (PGR). Thus, the objective of this experiment was to evaluate the use of Ascophyllum nodosum in the production of lawn seedlings, and growth regulators in the development of Carpet grass. The experiment was carried out between 2020 and 2021, and divided into two parts, the first being the production of seedlings (30 days) of Emerald grass, Bermudagrass DiscoveryTM, Carpet grass and Bahiagrass with the application of seaweed extract, in the second part the development of Carpet grass was evaluated after the application of PGRs (Trinexapac-ethy, Paclobutazol and Glyphosate) in 60 days. The evaluations performed were: green color index (GCI); normalized difference vegetation index (NDVI); root length and dry mass of seedlings. And for the second part: GCI; SPAD; NDVI; visual appearance; coverage rate; shoot height; growth rate and dry mass of clippings. It was observed that the use of the biostimulant increased the production of ornamental lawn plugs, where better values could be observed for Carpet grass. PGRs demonstrated efficient results for controlling the height of Carpet grass in up to 30 days, with emphasis on Trinexapac-ethyl, which reduced growth and maintained the aesthetics of the lawn.
Bioestimulante na produção de mudas de gramados e reguladores de crescimento no desenvolvimento da grama São Carlos
Keywords: Algae extract; Axonopus spp; Glyphosate; Paclobutrazol; Trinexapac-ethyl